ANALISIS PENILAIAN KINERJA TERHADAP SASARAN KERJA PEGAWAI SECARA ELEKTRONIK (STUDI KASUS PADA SUB BAGIAN UMUM DAN KEPEGAWAIAN BAPPEDA PROVINSI KALIMANTAN TIMUR) - M. Agus Hendra (ADMINISTRASI PUBLIK, 2019)
The goal of Employee Work electronically is an assessment carried out systematically based on predetermined standards to know the work results of employees efficiently within a certain period of time according to their duties and responsibilities that support the organization's goals.This study aims to find out and describe the Performance Assessment Analysis of Employee Work Electronically in the General and Personnel Section of the Bappeda in East Kalimantan Province along with the factors that hinder and support this influence.The results of the study and interviews of researchers regarding Performance Assessment Analysis of Employee Work Electronically in the General Subdivision and Staffing of Bappeda in East Kalimantan by using indicators based on work quantity, quality of work and work time of an individual in carrying out or working on a job. predetermined performance indicators are eligible to get the title "GOOD" this can be seen from the supporting factors, among others, employees understand more about the description of their respective duties, increased discipline of employees due to the responsibility of the target or work that must be produced according to the specified time and infrastructure that adequately supports the smooth running of employees in carrying out their assigned tasks. However, there are still things that must be considered because the inhibiting factors include limited human resources (HR) and lack of competency and educational qualifications of employees, and assessments are still very subjective because they are only assessed by superiors and do not involve other elements that.